Innovative Online Diagnostic Assessment for Evaluating Science Learning Readiness in the Merdeka Curriculum Framework - Widowati Pusporini; Dadan Rosana; Didik Setyawarno; Eko Widodo; Maryati Maryati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
The main objective of this study was to develop an Online Diagnostic Assessment (ODA) that can effectively measure junior high school students’ readiness to learn science within the framework of the Merdeka Curriculum. Unlike previous diagnostic tools that are mostly offline or limited in scope, this ODA provides an innovative, technology-based solution that identifies student readiness and misconceptions while offering timely feedback to support differentiated learning. Using the 4-D development model, the research includes the Define, Design, Develop, and Disseminate stages. At the Define stage, the instrument grids were identified according to the curriculum. In the Design stage, the assessment prototype was developed using Google Form. The Develop stage involved validation by experts and field tests in two junior high schools, resulting in a valid and reliable instrument, with an Aiken's V value above 0.80, Cronbach's Alpha 0.736, and McDonald's Omega 0.768. The results of the EFA analysis showed all items had Measures of Sampling Adequacy (MSA) of more than 0.5. The distribution of respondents' scores shows that the instrument is effective in differentiating students' abilities. Thus, the developed ODA is valid, reliable, and ready to be used to assess students' readiness in science learning.